Tractat de medicina per tots els ocells de caça. Introducció, anàlisi lèxica i edició. - I. MIRALLES, ANTONI MAS (Scripta, 2021)
This is a edition of an anonymous treatise on falconry, written in Catalan, and which can be, most probably, dated back to the 15 century. Manuscript 102, kept in the Library of the University of Barcelona, contains two texts: the first is Antoni Canals’ translation of a text by Petrarch, and the second a text which contains a set of medical prescriptions for game birds. This article consists of three parts: firstly, a short introduction on the writing and contents of the manuscript; secondly, an in-depth lexical analysis of the technical terminology on falconry divided into two parts: a proposal for the classification of the specific lexicon in the different semantic fields, and a glossary of the more relevant terms; and finally, a critical edition of this treatise on falconry.